Organizational Affiliation of Soccer Primer League 2020 – 2021 from the Players Point Of View - Khudair, Hamza Abdul Hussein; Mahdi, Ali Makki (Journal of Physical Education, 2021)
The research aimed at constructing a scale for organizational affiliation in soccer primer league coaches for the season 2020 – 2021 from the players’ point of view as well as identifying the reality of organizational affiliation in soccer primer league coaches from the players’ point of view. The problem of the research lies in the fear of being excluded from the training process and the lack of a scale that measures this type of affiliation. The researchers used the descriptive method on (370) soccer primer league players. The scale consisted of (24) items and after being applied to the subjects, the data was collected and treated using SPSS to conclude significant differences in the organizational affiliation in all fields. The researchers recommended using this scale due to its positive effect for enhancing affiliation in coaches.